STATUS GIZI DAN PERSEN LEMAK TUBUH BERHUBUNGAN DENGAN USIA MENARCHE ANAK SEKOLAH DASAR DI SD MUHAMMADIYAH GKB 1 GRESIK - Anisaul Makarimah; Lailatul Muniroh (Media Gizi Indonesia, 2017)
Menarche is first menstruation that an indicator of teenage girlsenter puberty phase. Nowadays the age of menarche has decreasedin tothe younger. The purpose of this study was to analyze the relation between nutritional status and body fat percentage with menarche age. This research used cross sectional design with sample size of 37 female students who had experienced menstruation and selected using simple random sampling. Data were collected by anthropometric measurements to assess nutritional status, body fat percentage using Bioelectrical Impedance Analysis (BIA). Data were analyzed by Spearman correlation test. The results showed that more than half of respondents had normal nutritional status (51.4%) and healthy body fat percentage. There was a correlation between nutritional status (p=0.029, r= -0.360) and body fat percentage (p =0.048, r=-0.328) with age of menarche among teenage girls at the Muhammadiyah GKB 1 Gresik Elementary School. The conclusion of this study was higher nutritional status (score of z-score) and fat percentage will decrease the age of menarche. Research suggestion is to normalize nutritional status and percent body fat. By maintaining consumption pattern and increase physical activity, such as cycling, swimming, and others.